2020
DOI: 10.1108/aia-03-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional perceptual antecedent can justify the social orienting deficit in autism spectrum disorder: an eye-tracking study

Abstract: Purpose Children with Autism Spectrum Disorder (ASD) show reduced attention to social stimuli. The reasons for these impairments are still being debated by researchers. The aim of this study is to analyse if reduced attention towards social stimuli is determined by initial underlying difficulties in the control of visual attention. Among the variables that could produce these difficulties, the authors considered geometric complexity and typology of geometric figures. Design/methodology/approach To test this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that flexibility deficits in ASD are related to repetitive behaviors in ASD. Inflexible adherence to specific routines, resistance to change, difficulty in transitions between different locations or events or circumscribed interests and inordinate preoccupation with particular objects or activities have commonly been observed in individuals with ASD (Baron-Cohen et al , 2013; Carrozza and Fabio, 2020; Fabio, 2012; Fabio et al , 2011). However, there is a lack of research in current literature on cognitive flexibility in ASD and the results of the few studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that flexibility deficits in ASD are related to repetitive behaviors in ASD. Inflexible adherence to specific routines, resistance to change, difficulty in transitions between different locations or events or circumscribed interests and inordinate preoccupation with particular objects or activities have commonly been observed in individuals with ASD (Baron-Cohen et al , 2013; Carrozza and Fabio, 2020; Fabio, 2012; Fabio et al , 2011). However, there is a lack of research in current literature on cognitive flexibility in ASD and the results of the few studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%